An empirical study on the impact of online word-of-mouth sources on retail sales. Issue 1 (20th February 2017) - Hong, Hong; Xu, Di; Xu, Dapeng; Wang, G. Alan; Fan, Weiguo
Abstract : Purpose: This study aims to analyze the impact of the source of online word-of-mouth (WOM) on retail sales. Specifically, the authors focus on the relative impact of external and internal WOMs on book sales. Design/methodology/approach: An empirical analysis is conducted with a panel data of sales and WOM for 87 books from Dangdang and Douban over a 14-day period based on two generalized least square regression models. Findings: Results suggest that both internal WOM and external WOM have significant impact on product sales, and the impact of external WOM is relatively more significant. Social implications: WOM, especially the external WOM, plays an important role in consumers' online purchase decisions. Originality/value: This study is helpful for retailers to better understand the factors influencing the sales and thereby forecast the future sales more precisely. Besides, the research conclusion could also enlighten related decision makers to constantly improve technical platforms.